Arduino-Based Data Acquisition Device Design for Specific Heat Determination of Hot Vegetable Oil - Redika Ardi Kusuma; Radi Radi; Arifin Dwi Saputro (The University of Lampung, 2023)
Vegetable oil is commonly used for cooking and frying at high temperatures. Information on the oil's specific heat in a process can help estimate the time and energy spent to reach a particular temperature. However, finding an accurate and affordable instrument for measuring specific heat at high temperatures was complex. This study aimed to design a prototype data acquisition device (DAQ) that can support the specific heat of high-temperature vegetable oil determination using the Joule experiment and Newton's correction. This study had two stages: prototype design/construction and prototype testing. The DAQ prototype consisted of a PZEM-003 power sensor, a PT100 temperature sensor, a relay, and an Arduino Mega 2560. The measurement results were displayed on an LCD and recorded in Microsoft data streamer. The prototype was tested by comparing the temperature, voltage, and current with commercial instruments resulting in accuracy and precision of 99.97% (99.95%), 99.97% (99.86%), and 99.99% (99.86 %), respectively. Performance tests showed that the specific heats of canola, corn, and sunflower oils at 100°C based on DAQ data analyzed separately were 2.119 J/kg.°C, 2.082 J/kg.°C, and 2.458 J/kg, respectively. The specific heat values were close to those in the reference, with an accuracy of 94.22%, 97.29%, and 99.80%, respectively. Keywords: ATmega2560, DAQ, Heat capacity, Hysteresis, Vegetable oil